TOTAL QUALITY MANAGEMENT (TQM) DALAM PENDIDIKAN SEBAGAI STRATEGI PENINGKATAN MUTU PENDIDIKAN: SYSTEMATIC LITERATURE REVIEW - Mahdini Al Ghifari; Serly Meilani; Feri Apriansah; Salfen Hasri; Sohiron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Improving the quality of education is one of the main challenges in the development of the education system in Indonesia. Various efforts have been made to improve the quality of educational services and outcomes, one of which is through the implementation of Total Quality Management (TQM). TQM is a management approach that emphasizes continuous improvement, customer focus, involvement of all organizational members, and data-based decision-making to achieve optimal quality. This study aims to analyze the implementation of TQM in education, identify its impact on the quality of educational institutions, and examine various obstacles faced in its implementation in Indonesia. The study used a systematic literature review method by analyzing various relevant scientific articles, books, and academic publications for the period 2016–2026. The analysis was conducted using a thematic synthesis approach to identify patterns of findings, research trends, and emerging research gaps in TQM studies in the field of education. The results of the study indicate that the implementation of TQM in education is generally realized through the application of the principles of customer focus, continuous improvement, quality leadership, involvement of all stakeholders, and strengthening the organization's quality culture. The implementation of TQM has been proven to have a positive impact on improving the quality of educational services, the effectiveness of institutional governance, the development of human resource competencies, and improving student learning outcomes. However, the implementation of TQM still faces various obstacles, such as a lack of understanding of the TQM concept, limited human resources, weak leadership commitment, resistance to change, and the challenges of digital transformation. Therefore, the successful implementation of TQM requires ongoing commitment, a strengthened culture of quality, and the support of all stakeholders to drive sustainable improvements in educational quality.